COMPARISON OF PAPER QUILLING AND PLAYDOUGH PLAYING ACTIVITIES TO THE FINE MOTOR DEVELOPMENT OF PRESCHOOL CHILDREN 4-5 YEARS AT AS-SHAFFAH KINDERGARTEN, BENGKULU CITY - Wewet Savitri; Diah Eka Nugraheni; Tania Aprilianti Fahlevi; Dwie Yunita Baska (Proceeding B-ICON, 2023)
Based on data from the Basic Health Research survey (Riskesdas, 2018), the index for children aged 36-59 months for the literacy aspect was 64.6%, physical 97.8%, social emotional 69.9%, learning aspect 95.2% and Indonesia's total development index in 2018 was 88.3% so that 11.7% of children aged 36-59 months experienced developmental disorders, where Bengkulu Province contributed to the prevalence of toddlers aged 36-59 months experiencing developmental disorders of 8.3%. The design of this study used Quasi-Experiment, taking samples using total sampling with a total sample of 40 people. This research method uses the Wilcoxon and Mann-Whitney tests. The results of the research showed that the average fine motor development score in the paper quilling group, the pre test score was from 8.40, increasing to 11.50 (post test score), with an average difference of 3.10, while in the playdough group the pre test score was 8. 60 increased by 10.60 (post test score) with an average difference of 2. The results of the Mann-Whitney test showed that the difference in the average pretest and posttest scores for the Paper Quilling group and the Playdough group was 0.9. This proves that providing paper quilling games can increase the average development score higher than playdough games.